Redes Sociais e turismo no Estado de Goiás: Contribuições da geolocalização para o desenvolvimento do setor turístico - Silveira, Alfredo Arantes Guimarães (2023)
The tourism sector has experienced significant growth over the last few decades, becoming one of the main players in international trade, representing one of the main sources of income for many developing countries, with tourism activities being one of the possibilities for achieving the Goals of Sustainable Development of the United Nations. In Brazil, the Ministry of Tourism has the National Tourism Plan as a benchmark for public policies in the sector, with emphasis on the Tourism Regionalization Program and the Brazilian Tourism Map, as essential tools for defining tourist regions in the States and for the inclusion of municipalities in the Tourism Map based on standardized criteria. In this sense, the research was guided by the hypothesis that the methodology established by the Ministry of Tourism for the inclusion of municipalities in the Brazilian Tourism Map could underestimate the existing tourist potential in the state of Goiás, since when basically considering administrative, normative and economic, undervalues the tourist attraction itself. The general objective of the thesis is to evaluate the existence of nature tourism attractions in the state of Goiás through geolocation data existing on the world wide web, aiming to subsidize policies for the development of the tourism sector. Having the state of Goiás as a territorial focus and as an object of analysis, the locations and activities that have synergy with nature tourism, spatial analyzes were carried out from posts on the social network Instagram with associated geotags, cartographic bases and official information from agencies public and also cartographic bases built in collaborative mapping processes, with the purpose of confronting the tourist potential mapped with the presence or absence of Goiás municipalities in the Brazilian Tourism Map of the year 2022. The result achieved consolidated the diagnosis that municipalities with environments that have synergy with activities aimed at nature tourism were not included in the Brazilian Tourism Map of the year 2022, confirming the hypothesis that the methodology established by the Brazilian Ministry of Tourism for the insertion of municipalities in the Tourism Map undersizes the existing tourist potential, by considering only administrative, normative and economic criteria, to the detriment of the protagonist of the tourist potential, the tourist attraction, the one that motivates the tourist to move, seeking rest, leisure and quality of life through contact with nature.